Conserved function of bat TBK1 in activating innate immunity against RNA viruses: insights into the innate immune response in bats - Liu, Qiuju; Shao, Qi; Xu, Caixia; Liu, Chao; Li, Shuhan; Wang, Jie; Liu, Xia; Zhang, Kehui; Yan, Yaxian; Sun, Jianhe; Cheng, Yuqiang (Frontiers in Immunology, 2025)
Bats exhibit unique abilities to coexist with viruses asymptomatically, setting them apart among mammals. The innate immune system serves as the primary defense against pathogens. As a crucial central node protein in this system, TANK binding kinase 1(TBK1) can receive signals from multiple pattern recognition receptors (PRRs), and then promote the production of Type I interferon (IFN I) and inflammatory factors. Despite its importance, how TBK1 works in bats remains poorly understood. Here, through bioinformatics analysis, TBK1 was found to exhibit a high sequence conservation across species. Overexpression of bat TBK1 significantly upregulated IFNβ expression, and then inhibited viral replication. Co-expression of bat TBK1 with bat IRF1/3/7 can facilitate the upregulation of IFNβ mediated by bat TBK1, implying the activation signals potentially can be transmitted from bat TBK1 to IRF1/3/7, and then promote IFNβ production. Structurally, protein kinase domain (PKD), ubiquitin-like domain (ULD), and coiled-coil domain 1 (CCD1) are essential domains for bat TBK1 to function normally. In summary, this study elucidated bat TBK1 has a conserved ability to activate bat antiviral innate immunity.